Cathode material of medium-temperature solid oxide fuel cell as well as preparation method and application of cathode material
By doping the surface of the SOFC cathode material with a platinum coating, the problems of insufficient catalytic activity, poor stability and low transmission efficiency of the cathode material under medium temperature conditions are solved, and the catalytic activity and stability of the material are significantly improved.
Patent Information
- Application Number
- CN202411441683.4
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-10-15
- Publication Date
- 2025-01-24
AI Technical Summary
Under medium temperature conditions, SOFC cathode materials have problems such as insufficient catalytic activity, poor stability and low transmission efficiency.
By doping cornering platinum on the surface of the cathode material to form a doped coating layer to improve the electronic structure and oxygen reaction activity site on the surface of the material surface.
The catalytic activity and stability of the cathode material are significantly improved, the activation energy of the oxygen reduction reaction is reduced, the electronic conductivity is enhanced, and the service life of the material is extended.
Smart Images

Figure CN119361728A_ABST
Abstract
Description
Technical Field
[0001] The present application relates to the field of fuel cell technology, and in particular to cathode materials for medium-temperature solid oxide fuel cells, and preparation methods and applications thereof. Background Art
[0002] Solid oxide fuel cells, as an efficient and clean energy conversion device, play an extremely important role in the energy field. However, current SOFCs still face many challenges in practical applications.
[0003] First, conventional SOFC cathode materials have insufficient catalytic activity under medium temperature conditions. Under medium temperature conditions (usually 600-800°C), the rate of oxygen reduction reaction is relatively low. This is mainly because the cathode surface has limited adsorption and dissociation capacity for oxygen molecules, resulting in a high activation energy for oxygen reduction reaction, which greatly affects the overall performance of the battery.
[0004] Secondly, the stability of the cathode material is also a key issue. During long-term operation at medium temperature, the cathode material may undergo structural phase change, surface oxidation, element segregation and other undesirable phenomena. These changes will cause the performance of the material to gradually decline, such as a decrease in ionic conductivity and electronic conductivity, and an increase in polarization resistance.
[0005] In addition, the transmission efficiency of ions and electrons in the cathode material is also an important factor restricting the performance of SOFC. At medium temperature, if the transmission speed of ions and electrons is not fast enough, the resistance inside the battery will increase, thereby reducing the output power and energy conversion efficiency of the battery. The ion and electron transmission channels of traditional materials may be defective or blocked, making it difficult to achieve efficient transmission. Summary of the invention
[0006] The present application provides a cathode material for a medium-temperature solid oxide fuel cell, a preparation method thereof, and an application thereof, so as to improve the catalytic activity and stability of the cathode material under medium-temperature conditions.
[0007] In a first aspect, the present application provides a cathode material for a medium-temperature solid oxide fuel cell, the cathode material comprising a cathode material body and a doped coating layer coated on the cathode material body, the cathode material body comprising a perovskite material, and the doped coating layer material comprising platinum.
[0008] As an optional implementation manner, the mass ratio of the platinum to the perovskite material is 1:(40.6-121.8).
[0009] As an optional implementation, the perovskite material includes a bulk-doped LaMnO3 type perovskite material.
[0010] As an optional implementation, the perovskite material includes a LaMnO3 type perovskite material doped with Sr in the bulk phase.
[0011] As an optional implementation, the perovskite material includes a LaMnO3 type perovskite material doped with Co in the bulk phase.
[0012] As an optional embodiment, the perovskite material includes (La 1-x Sr x )(Mn 1-y Co y )O3, where 0<x≤1, 0<y≤1.
[0013] As an optional implementation, 0.08≤x≤0.15; and / or
[0014] 0.18≤y≤0.22.
[0015] In a second aspect, the present application provides a method for preparing a cathode material of a medium-temperature solid oxide fuel cell, wherein the stress material is the cathode material provided in the first aspect; the method comprises:
[0016] obtaining a cathode material body, wherein the cathode material body comprises a perovskite material;
[0017] Platinum is doped into the surface of the cathode material body to form a doped coating layer to obtain the cathode material.
[0018] As an optional implementation, the method of doping platinum into the surface of the cathode material body includes at least one of chemical vapor deposition, impregnation, atomic layer deposition, sol-gel method and ion implantation method.
[0019] In a third aspect, the present application provides a medium-temperature solid oxide fuel cell, wherein the fuel cell comprises the cathode material provided in the first aspect.
[0020] The above technical solution provided by the embodiment of the present application has the following advantages compared with the prior art:
[0021] The cathode material provided in the embodiment of the present application improves the electronic structure of the material surface, improves the electronic conductivity, and makes the transmission of electrons on the surface smoother by doping and coating platinum on the surface of the cathode material body. Platinum provides a large number of efficient oxygen reduction reaction active sites on the surface of the cathode material body, and platinum has a unique electronic structure, which can greatly accelerate the adsorption and dissociation process of oxygen molecules, significantly reduce the activation energy of the oxygen reduction reaction, and greatly improve the catalytic activity of the entire cathode material. At the same time, the platinum on the surface of the cathode material body forms a stable protective layer under medium temperature environment, which effectively prevents oxidation, corrosion and other problems on the surface of the material, maintains the chemical and structural stability of the surface, and prolongs the service life of the material. BRIEF DESCRIPTION OF THE DRAWINGS
[0022] The accompanying drawings, which are incorporated in and constitute a part of this specification, illustrate embodiments consistent with the present application and, together with the description, serve to explain the principles of the present application.
[0023] In order to more clearly illustrate the embodiments of the present application or the technical solutions in the prior art, the drawings required for use in the embodiments or the description of the prior art will be briefly introduced below. Obviously, for ordinary technicians in this field, other drawings can be obtained based on these drawings without paying any creative labor.
[0024] Figure 1 A flowchart of the method provided in the embodiment of the present application. DETAILED DESCRIPTION
[0025] In order to make the purpose, technical solution and advantages of the embodiments of the present application clearer, the technical solution in the embodiments of the present application will be clearly and completely described below in conjunction with the drawings in the embodiments of the present application. Obviously, the described embodiments are part of the embodiments of the present application, not all of the embodiments. Based on the embodiments in the present application, all other embodiments obtained by ordinary technicians in this field without making creative work are within the scope of protection of this application.
[0026] Unless otherwise specified, various raw materials, reagents, instruments and equipment used in this application can be purchased from the market or prepared by existing methods.
[0027] At present, under medium temperature conditions, SOFC cathode materials have problems such as insufficient catalytic activity, poor stability, and low transmission efficiency.
[0028] The applicant has found that layered doping of the surface and bulk of the cathode material can improve the above-mentioned problems.
[0029] As for surface doping, it can directly change the contact interface between the cathode material and oxygen by introducing specific elements or compounds on the surface of the material. These doping substances can form abundant active sites on the surface, greatly enhance the adsorption capacity of oxygen molecules on the cathode surface, accelerate the dissociation process of oxygen molecules, thereby reducing the activation energy of the oxygen reduction reaction and significantly improving the catalytic activity of the cathode material. At the same time, surface doping can also adjust the electronic structure and chemical properties of the surface, prevent oxidation and corrosion of the surface in a medium temperature environment, and maintain the stability of the surface.
[0030] In terms of bulk doping, by doping appropriate elements into the material, the crystal structure and electronic structure of the material can be fundamentally adjusted. On the one hand, reasonable bulk doping can optimize the ionic conductivity and electronic conductivity of the material, providing a smoother channel for the transmission of ions and electrons within the material. The concentration and distribution of oxygen vacancies in the crystal structure can be changed by doping elements, promoting the transmission of oxygen ions. On the other hand, bulk doping can also enhance the overall structural stability of the material, reduce structural phase changes and performance degradation caused by factors such as thermal stress and chemical reactions, and enable the cathode material to maintain stable performance during long-term operation at medium temperature.
[0031] Therefore, the present application intends to provide a cathode material for a medium-temperature solid oxide fuel cell, by adopting surface and bulk layered doping to improve the catalytic activity, stability and transmission efficiency of the cathode material under medium-temperature conditions.
[0032] An embodiment of the present application provides a cathode material for a medium-temperature solid oxide fuel cell, wherein the cathode material comprises a cathode material body and a doped coating layer coated on the cathode material body, wherein the cathode material body comprises a perovskite material, and the doped coating layer material comprises platinum.
[0033] The cathode material improves the electronic structure of the material surface, increases the electronic conductivity, and makes the transmission of electrons on the surface smoother by doping and coating platinum on the surface of the cathode material. Platinum provides a large number of efficient active sites for oxygen reduction reactions on the surface of the cathode material, and platinum has a unique electronic structure that can greatly accelerate the adsorption and dissociation process of oxygen molecules, significantly reduce the activation energy of the oxygen reduction reaction, and greatly improve the catalytic activity of the entire cathode material. At the same time, the platinum on the surface of the cathode material forms a stable protective layer under medium temperature conditions, which effectively prevents oxidation and corrosion on the surface of the material, maintains the chemical and structural stability of the surface, and extends the service life of the material.
[0034] In some embodiments, the mass ratio of the platinum to the perovskite material is 1:(40.6-121.8). By controlling the mass ratio of platinum to the perovskite material within a suitable range, the performance and cost of the entire cathode material can be taken into consideration.
[0035] In some embodiments, the perovskite material includes a LaMnO3-type perovskite material (i.e., ABO3 type, the A position and B position described below are the corresponding positions in the structural formula) with bulk doping. LaMnO3 has a typical perovskite structure, which has high stability and controllability. The A-site and B-site ions in the perovskite structure can be replaced by different elements and doped to adjust the performance of the material. Under certain conditions, LaMnO3 has good oxygen ion conductivity, which is very important for the cathode material of solid oxide fuel cells, and can promote the transport of oxygen ions in the cathode and participate in electrochemical reactions.
[0036] In some embodiments, the perovskite material includes a LaMnO3-type perovskite material doped with Sr in the bulk phase. The ionic radius of Sr is different from that of La. Doping Sr can change the lattice parameters of the crystal structure, optimize the diffusion channel of oxygen ions, facilitate the transmission of oxygen ions under medium temperature conditions, and improve the ionic conductivity. At the same time, Sr doping can enhance the structural stability of the material, reduce phase changes and performance degradation during long-term operation at medium temperature. For example, Sr can form more stable chemical bonds with the surrounding oxygen ions and improve the material's antioxidant capacity. In addition, an appropriate amount of Sr doping can adjust the electronic structure of the material, increase the carrier concentration, and improve the electronic conductivity, thereby improving the electrochemical properties of the cathode material as a whole.
[0037] In some embodiments, the perovskite material includes a LaMnO3-type perovskite material doped with Co in the bulk phase. Co has rich valence states and good catalytic activity. Co doping at the B position can provide more active sites for the oxygen reduction reaction, accelerate the adsorption and dissociation process of oxygen molecules on the cathode surface, reduce the activation energy of the oxygen reduction reaction, and improve the catalytic performance of the cathode. At the same time, Co doping can improve the electronic structure of the material, increase the mobility and carrier concentration of electrons, improve the electronic conductivity, and facilitate the transmission of electrons in the cathode material. In addition, Co doping can enhance the structural stability of the material and improve the durability of the material under medium temperature conditions. For example, Co can form a stable solid solution with Mn to reduce structural changes caused by thermal stress and chemical reactions.
[0038] In some embodiments, the perovskite material includes (La 1-x Sr x )(Mn 1-y Co y )O3, wherein 0<x≤1, 0<y≤1. By controlling the doping amount of Sr and Co within a certain range, the stability of the crystal structure of the entire material and the performance of the material can be taken into account. Furthermore, 0.08≤x≤0.15; 0.18≤y≤0.22.
[0039] Figure 1A flow chart of the method provided in the embodiment of the present application is as follows: Figure 1 As shown, based on a general inventive concept, the embodiment of the present application also provides a method for preparing a cathode material of a medium-temperature solid oxide fuel cell, wherein the stress material is the cathode material provided above; the method comprises:
[0040] S1. Obtaining a cathode material body, wherein the cathode material body comprises a perovskite material;
[0041] S2. doping platinum onto the surface of the cathode material body to form a doped coating layer to obtain a cathode material.
[0042] This method is used to prepare the above-mentioned cathode material. The specific content of the cathode material can refer to the above-mentioned embodiment. Since this method adopts part or all of the technical solutions of the above-mentioned embodiment, it at least has all the beneficial effects brought by the technical solutions of the above-mentioned embodiment, which will not be repeated here one by one.
[0043] In some embodiments, the method of doping platinum into the surface of the cathode material body includes at least one of chemical vapor deposition, impregnation, atomic layer deposition, sol-gel method and ion implantation method.
[0044] Based on a general inventive concept, an embodiment of the present application further provides a medium-temperature solid oxide fuel cell, wherein the fuel cell includes the cathode material provided in the first aspect.
[0045] The fuel cell is realized based on the above-mentioned cathode material. The specific content of the cathode material can refer to the above-mentioned embodiment. Since the fuel cell adopts part or all of the technical solutions of the above-mentioned embodiments, it has at least all the beneficial effects brought by the technical solutions of the above-mentioned embodiments, which will not be repeated here one by one.
[0046] The present application will be further described below in conjunction with specific embodiments. It should be understood that these embodiments are intended only to illustrate the present application and are not intended to limit the scope of the present application. The experimental methods for which specific conditions are not specified in the following examples are usually measured according to national standards. If there is no corresponding national standard, then the conditions recommended by the manufacturer are followed.
[0047] Example 1
[0048] A surface and bulk co-doped medium-temperature SOFC cathode material, comprising a cathode material body and a doped coating layer coated on the cathode material body, wherein the cathode material body comprises a perovskite material, and the perovskite material comprises (La 1-x Sr x )(Mn 1-y Co y)O3, wherein x=0.1, y=0.2, the doped coating layer material includes platinum, and the mass ratio of the doping amount of platinum to the perovskite material is 1:40.6.
[0049] The preparation process is as follows:
[0050] Bulk doping step: Weigh La2O3, SrCO3, MnO2, and Co3O4 powders accurately according to the stoichiometric ratio. Put the powder into a ball mill, use zirconium oxide balls as grinding balls, and the ball-to-material ratio is 3:1. Ball milling is carried out at a speed of 300 rpm for 6 hours. During the ball milling process, an appropriate amount of anhydrous ethanol is added as a dispersant. The mixed powder after ball milling is placed in a box-type resistance furnace, and the temperature is increased to 900℃ at a heating rate of 5℃ / min. It is pre-burned at this temperature for 4 hours. The pre-burned material is taken out and cooled, and then ground again to make its particles finer and more uniform.
[0051] Surface doping step: Pt doping is performed using chemical vapor deposition (CVD). The bulk-doped material is placed in a CVD device, and the Pt precursor is decomposed and deposited on the material surface under a specific temperature of 500°C and atmosphere (the atmosphere is a mixture of hydrogen and argon, the ratio of hydrogen to argon is 1:4, the total gas flow rate is 100 sccm (standard cubic centimeters per minute), the hydrogen flow rate is 20 sccm, and the argon flow rate is 80 sccm).
[0052] The stress material is prepared into an electrode, and the process is as follows: the prepared cathode material powder is mixed with an appropriate amount of a binder (ethyl cellulose) and a dispersant (pinene alcohol) to make a slurry, the slurry is coated on the electrolyte surface by screen printing, and then the temperature is increased to 1000°C at a heating rate of 2°C / min in a box-type resistance furnace, and the electrode is sintered for 2 hours to form a dense cathode layer.
[0053] Example 2
[0054] A surface and bulk co-doped medium-temperature SOFC cathode material, comprising a cathode material body and a doped coating layer coated on the cathode material body, wherein the cathode material body comprises a perovskite material, and the perovskite material comprises (La 1-x Sr x )(Mn 1-y Co y )O3, wherein x=0.15, y=0.18, the doped coating layer material includes platinum, and the mass ratio of the doping amount of platinum to the perovskite material is 1:40.6.
[0055] The preparation process is as follows:
[0056] Bulk doping step: Weigh La2O3, SrCO3, MnO2, and Co3O4 powders accurately according to the stoichiometric ratio. Put them into a planetary ball mill with agate balls and a ball-to-material ratio of 2.5:1. Mill at 250 rpm for 8 hours, and add a small amount of acetone to enhance the dispersion effect. Heat to 950°C in a muffle furnace at a heating rate of 4°C / min and pre-sinter for 5 hours. Cool after pre-sintering and grind again.
[0057] Surface doping step: Pt doping is performed by impregnation. The bulk-doped material is immersed in a solution containing a Pt precursor, stirred evenly, and allowed to stand for a period of time, then taken out and dried, and calcined at an appropriate temperature, wherein the drying temperature is 100°C and the calcination temperature is 400°C.
[0058] The stress material is prepared into an electrode, and the process is as follows: the prepared cathode material powder is mixed with an appropriate amount of a binder (ethyl cellulose) and a dispersant (pinene alcohol) to make a slurry, the slurry is coated on the surface of the electrolyte by spraying, and the slurry is placed in a box furnace and heated to 1050°C at a heating rate of 3°C / min, and sintered for 1.5 hours to form a dense cathode layer.
[0059] Example 3
[0060] A surface and bulk co-doped medium-temperature SOFC cathode material, comprising a cathode material body and a doped coating layer coated on the cathode material body, wherein the cathode material body comprises a perovskite material, and the perovskite material comprises (La 1-x Sr x )(Mn 1-y Co y )O3, wherein x=0.1, y=0.2, the doped coating layer material includes platinum, and the mass ratio of the doping amount of platinum to the perovskite material is 1:121.8.
[0061] The preparation process is as follows:
[0062] Bulk doping step: Weigh La2O3, SrCO3, MnO2, and Co3O4 powders accurately according to the stoichiometric ratio. Put the powder into a high-energy ball mill, use stainless steel balls as grinding balls, and the ball-to-material ratio is 2:1. Ball mill at a speed of 400 rpm for 5 hours, and add an appropriate amount of isopropanol to assist dispersion. Heat to 880°C in a tubular furnace at a heating rate of 6°C / min and pre-sinter for 3.5 hours. Take out the pre-sintered material and grind it to refine its particles.
[0063] Surface doping step: Pt doping is performed using atomic layer deposition (ALD). The bulk-doped material is placed in the ALD equipment, the deposition parameters are precisely controlled, and the deposition temperature is 250°C, so that Pt is evenly deposited on the material surface.
[0064] The stress material is prepared into an electrode, and the process is as follows: the prepared cathode material powder is mixed with an appropriate amount of a binder (ethyl cellulose) and a dispersant (pinene alcohol) to make a slurry, the slurry is coated on the electrolyte surface by screen printing, and then the temperature is increased to 1020°C at a heating rate of 2.5°C / min in a box-type resistance furnace, and the temperature is kept and sintered for 1.8 hours to form a dense cathode layer.
[0065] Example 4
[0066] A surface and bulk co-doped medium-temperature SOFC cathode material, comprising a cathode material body and a doped coating layer coated on the cathode material body, wherein the cathode material body comprises a perovskite material, and the perovskite material comprises (La 1-x Sr x )(Mn 1-y Co y )O3, wherein x=0.12, y=0.2, the doped coating layer material includes platinum, and the mass ratio of the doping amount of platinum to the perovskite material is 1:60.9.
[0067] The preparation process is as follows:
[0068] Bulk doping step: Weigh La2O3, SrCO3, MnO2, and Co3O4 powders accurately according to the stoichiometric ratio. Put the powders into a vibrating ball mill, use carbide balls, and a ball-to-material ratio of 3.5:1, and ball mill at 350 rpm for 7 hours. Add a small amount of ethanolamine as a dispersant. Heat to 920℃ in a high-temperature box furnace at a heating rate of 4.5℃ / min and pre-sinter for 4.5 hours. Cool the pre-sintered material and grind it again.
[0069] Surface doping step: Pt doping is performed by sol-gel method combined with post-treatment. First, a sol containing a Pt precursor is prepared, and the bulk-doped material is immersed in the sol, and then dried, calcined, and other steps are performed. The drying temperature is 80°C, the calcination temperature is 500°C, and the drying and calcination processes are performed in an air atmosphere.
[0070] The stress material was prepared into an electrode, and the process was as follows: the prepared cathode material powder was mixed with an appropriate amount of binder (ethyl cellulose) and dispersant (pinene alcohol) to make a slurry, the slurry was coated on the electrolyte surface by screen printing, and then placed in a tubular furnace and heated to 1030°C at a heating rate of 2°C / min, and sintered for 1.6 hours to form a dense cathode layer.
[0071] Example 5
[0072] A surface and bulk co-doped medium-temperature SOFC cathode material, comprising a cathode material body and a doped coating layer coated on the cathode material body, wherein the cathode material body comprises a perovskite material, and the perovskite material comprises (La 1-x Sr x )(Mn 1-y Co y )O3, wherein x=0.13, y=0.19, the doped coating layer material includes platinum, and the mass ratio of the doping amount of platinum to the perovskite material is 1:60.9.
[0073] The preparation process is as follows:
[0074] Bulk doping step: Weigh La2O3, SrCO3, MnO2, and Co3O4 powders accurately according to the stoichiometric ratio. Put the powders into a horizontal ball mill, use zirconium oxide balls as grinding balls, and the ball-to-material ratio is 2.8:1. Mill at a speed of 320 rpm for 7.5 hours, and add an appropriate amount of ethylene glycol as a dispersant. Heat to 860°C in a muffle furnace at a heating rate of 5.5°C / min and pre-sinter for 4 hours. Grind the pre-sintered material again.
[0075] Surface doping step: Pt doping is performed by ion implantation. The bulk doped material is placed in an ion implantation device. The ion implantation process does not require a high temperature environment, but annealing may be required after ion implantation to repair the lattice damage caused by ion implantation. The annealing temperature is 600°C. The ion implantation process is performed under vacuum with a vacuum degree of 10 -6 Pa, implanting Pt ions into the material surface.
[0076] The stress material was prepared into an electrode, and the process was as follows: the prepared cathode material powder was mixed with an appropriate amount of binder (ethyl cellulose) and dispersant (pinene alcohol) to make a slurry, the slurry was coated on the electrolyte surface by screen printing, and then the temperature was increased to 1040°C in a box furnace at a heating rate of 2.2°C / min and sintered for 1.7 hours to form a dense cathode layer.
[0077] Comparative Example 1
[0078] Undoped LaMnO3 material, and the same electrode preparation process as in Example 1 is used.
[0079] Comparative Example 2
[0080] Compared with Example 1, no surface doping was performed (ie, there was no platinum on the surface), and the same electrode preparation process as Example 1 was adopted.
[0081] Electrodes prepared from the cathode materials provided in the embodiments and comparative examples were subjected to electrochemical tests, and the results are shown in the following table:
[0082]
[0083]
[0084] It can be seen from the above table that the cathode material provided in the embodiments of the present application has good catalytic activity and stability under medium temperature conditions.
[0085] Various embodiments of the present application may be presented in the form of a range; it should be understood that the description in the form of a range is only for convenience and brevity, and should not be understood as a rigid limitation on the scope of the present application; therefore, the range description should be considered to have specifically disclosed all possible sub-ranges and single numerical values within the range. For example, the range description from 1 to 6 should be considered to have specifically disclosed sub-ranges, such as from 1 to 3, from 1 to 4, from 1 to 5, from 2 to 4, from 2 to 6, from 3 to 6, etc., as well as single numbers within the range, such as 1, 2, 3, 4, 5 and 6, which apply regardless of the range. In addition, whenever a numerical range is indicated herein, it is meant to include any cited number (fractional or integer) within the indicated range.
[0086] In the present application, in the absence of any contrary description, the directional words used, such as "upper" and "lower", are specifically the directions of the drawings in the accompanying drawings. In addition, in the description of the present specification, the terms "including", "comprising", etc. refer to "including but not limited to". In this article, relational terms such as "first" and "second" are only used to distinguish one entity or operation from another entity or operation, and do not necessarily require or imply that there is any such actual relationship or order between these entities or operations. In this article, "and / or" describes the association relationship of the associated objects, indicating that there may be three relationships, for example, A and / or B, which can represent: A exists alone, A and B exist at the same time, and B exists alone. Wherein A, B can be singular or plural. In this article, "at least one" refers to one or more, and "plural" refers to two or more. "At least one", "at least one of the following" or similar expressions refer to any combination of these items, including any combination of singular or plural items. For example, "at least one of a, b or c", or "at least one of a, b and c", can both mean: a, b, c, ab (i.e. a and b), ac, bc, or abc, where a, b and c can be single or multiple, respectively.
[0087] The above description is only a specific implementation of the present application, so that those skilled in the art can understand or implement the present application. Various modifications to these embodiments will be apparent to those skilled in the art, and the general principles defined herein can be implemented in other embodiments without departing from the spirit or scope of the present application. Therefore, the present application will not be limited to the embodiments shown herein, but will conform to the widest range consistent with the principles and novel features applied for herein.
Claims
1. A cathode material for a medium-temperature solid oxide fuel cell, characterized in that: The cathode material comprises a cathode material body and a doped coating layer coated on the cathode material body, the cathode material body comprises a perovskite material, and the doped coating layer material comprises platinum.
2. The cathode material for medium-temperature solid oxide fuel cell according to claim 1, characterized in that: The mass ratio of the platinum to the perovskite material is 1:(40.6-121.8).
3. The cathode material for the medium-temperature solid oxide fuel cell according to claim 1, characterized in that: The perovskite material includes a bulk-doped LaMnO3 type perovskite material.
4. The cathode material for the medium-temperature solid oxide fuel cell according to claim 3, characterized in that: The perovskite material includes a LaMnO3 type perovskite material doped with Sr in the bulk phase.
5. The cathode material for the medium-temperature solid oxide fuel cell according to claim 3, characterized in that: The perovskite material includes a LaMnO3 type perovskite material doped with Co in the bulk phase.
6. The cathode material for the medium-temperature solid oxide fuel cell according to claim 1, characterized in that: The perovskite material includes (La 1-x Sr x )(Mn 1-y Co y )O3, where 0<x≤1, 0<y≤1.
7. The cathode material for the medium-temperature solid oxide fuel cell according to claim 6, characterized in that: 0.08≤x≤0.15; and / or 0.18≤y≤0.22。 8. A method for preparing a cathode material for a medium-temperature solid oxide fuel cell, characterized in that: The stress material is a cathode material as described in any one of claims 1 to 7; the method comprises: obtaining a cathode material body, wherein the cathode material body comprises a perovskite material; Platinum is doped into the surface of the cathode material body to form a doped coating layer to obtain the cathode material.
9. The method for preparing a cathode material for a medium-temperature solid oxide fuel cell according to claim 8, characterized in that: The method of doping platinum into the surface of the cathode material body includes at least one of chemical vapor deposition, impregnation, atomic layer deposition, sol-gel method and ion implantation method.
10. A medium-temperature solid oxide fuel cell, characterized in that: The fuel cell comprises the cathode material according to any one of claims 1 to 7.
Citation Information
Cited By
Lithium manganese iron phosphate film positive electrode material and preparation method thereof
CN121076121A
Lithium iron manganese phosphate thin film positive electrode material and preparation method thereof
CN121076121B